The effect of Centella asiatica (L.) Urban on the organotypic model of spinal cord injury - Nur Nabilah Ahmad Puzi,; Yogeswaran Lokanathan,; Ruszymah Hj. Idrus, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Centella asiatica (L.) Urban (CA) is a well- known plant used to improve brain and memory functions in traditional medicine. Scientifically it was proven to show neurogenic effect on neural cell lines and in rat’s hippocampus. Its effect on spinal cord (SC) neurons, however, have not been studied. Aim of this study was to investigate the effects of raw extract of CA (RECA) on neurite outgrowths in an organotypic model of SC injury (OMSCI). OMSCI was prepared using SC slices obtained from postnatal-day 8 rat pups. Spinal cord tissues were embedded in gelatine gel and sliced to produce 300 μm thick slices. These slices were 100% viable for 8 days in culture. RECA, in concentrations of 0-800 μg/mL was added to the OMSCI media for 7 days, followed by immunostaining for TUJ-1 and GFAP. The investigated parameters were mean neurite count, mean neurite length, mean longest neurite and growth ratio. The tested RECA concentrations showed no cytotoxicity. ANOVA and Kruskal-Wallis tests showed no significant difference between groups in all the tested parameters. This may be due to low content of neurotrophic bioactive compounds content in the extract, which probably due to differences in geographical location, extraction method and absence of neurotrophic factors in the media. In conclusion, the tested RECA concentration were found to be safe; but without notable neurotrophic effects on the spinal cord organotypic model as demonstrated in this study.